PsycEXTRA Dataset 2013
DOI: 10.1037/e633262013-688
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Animacy and Noun-Phrase Relatedness on the Processing of Complex Sentences

Abstract: Previous work has suggested that syntactically complex object-extracted relative clauses are easier to process when the head noun phrase (NP1) is inanimate and the embedded noun phrase (NP2) is animate compared to the reverse animacy configuration, with differences in processing difficulty beginning as early as NP2 (e.g., The article that the senator… versus The senator that the article…). Two eye-tracking-while-reading experiments were conducted to better understand the source of this effect. Experiment 1 sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The effect of whether the comprehension probe targeted the main or relative clause was also replicated. While not theoretically relevant to meter-syntax alignment, this effect appears to be strong and robust at least within the current paradigm and from what we can gather, surprisingly few studies have addressed this topic (Lowder & Gordon, 2014;Newman et al, 2009). Unlike experiment 1, we additionally had participants tap their finger in time with the metrical beat.…”
Section: Discussionmentioning
confidence: 78%
“…The effect of whether the comprehension probe targeted the main or relative clause was also replicated. While not theoretically relevant to meter-syntax alignment, this effect appears to be strong and robust at least within the current paradigm and from what we can gather, surprisingly few studies have addressed this topic (Lowder & Gordon, 2014;Newman et al, 2009). Unlike experiment 1, we additionally had participants tap their finger in time with the metrical beat.…”
Section: Discussionmentioning
confidence: 78%
“…Although many previous studies have reported ORC‐SRC effects at the matrix verb (e.g., Gordon et al., 2001, 2004, 2006; Johnson et al., 2011; King & Just, 1991; Lowder & Gordon, 2012, 2014, 2016; Traxler et al., 2002, 2005; cf. Staub, 2010), these experiments have virtually always positioned the matrix verb immediately after the RC, thus making it difficult to determine whether effects at the matrix verb reflect memory‐retrieval processes, as has been argued (for a review, see Gordon & Lowder, 2012), or spillover effects from the RC.…”
Section: Discussionmentioning
confidence: 99%
“…A cleaner comparison can be found at the matrix verb, where the two structures are once again identical. Indeed, many previous experiments have found evidence that ORCs are more difficult to process than SRCs at the matrix verb (e.g., Gordon et al., 2001, 2004, 2006; Johnson et al., 2011; King & Just, 1991; Lowder & Gordon, 2012, 2014, 2016; Traxler, Morris, & Seely, 2002; Traxler, Williams, Blozis, & Morris, 2005; cf. Staub, 2010).…”
Section: Introductionmentioning
confidence: 99%